Estudio de los costos de la producción de jícama aplicando la NIC 41 en el centro experimental y de producción Salache Universidad Técnica de Cotopaxi - Gallardo Gallardo, Gloria Amparo (2017)
The present work is the result of the information compilation regarding the costs of the production of Jícama in the Experimental and Salache Production Center of the Technical University of Cotopaxi. The type of research was quantitative, for which we used scientific methods, deductive - inductive that allowed us to start from specific parts such as the existence of documentation and the analytical that was used to analyze the data granted by the Institution. To obtain results, surveys were applied to the people directly involved in the Jícama crop project, allowing this technique to give an analysis of the results and interpret and understand the problem that the Institution had. Product of the research field work of the Salache Experimental and Production Center, and to implement the following simulation of costs that was done by the research group, which will allow an efficient control of each of the expenses incurred, to That allows to know clarity the Total and Unitary Cost, of the kilogram of Jícama. Besides that it will help the diversification of the crop in new alternatives projecting itself to the export and sale, since at present it is a little known product and it is unknown of its benefits and benefits that presents….